Entidades políticas e individuación - Sirias Arroyo, Jean Carlos (2020)
This paper examines the pertinence of the Spinozian theory of composed individual in the ambit of political entities. It presents a revision of the Ethics and the Letter 32. The objective is to show that the theory of composed individual is not-sufficient to consider the political entities as individuals.